"Labor is Noble and Holy": Ironic Inclusion and Exclusion in the Knights of Labor, 1885-1890. Issue 3 (3rd July 2019) - Keohane, Jennifer
Abstract : During the 1880s, the Knights of Labor united most workers regardless of craft or trade. They also organized African American workers and women. This essay uncovers how the Knights maintained unity by analyzing speeches given at their annual conventions from 1885-1890. Leaders defined male Knights as chivalric, self-sacrificing, and battle-tested. After identifying the elements of the rhetoric of knighthood, I then explain how the rhetoric offered only ironic inclusion to white women and excluded Chinese and Eastern European immigrants. This argument builds rhetorical scholarship on inclusion and exclusion in social movements by theorizing its partial and ironic modes.